CONFLICT BETWEEN THEM: CRITICAL ANALYSIS OF MASK-WEARING ISSUES REGULATION IN CNN - Agis - Andriani; Angelica Monalisa; Tasya Meita (Undiksha Press, 2022)
COVID-19 has been declared a pandemic by World Health Organization (WHO). Coronavirus disease transmission mainly occurs through exposure to respiratory droplets on exhalation and in close contact with COVID-19 patients. For this reason, the local governments in many countries made the mandatory masks, following the guidelines of WHO. Masks become the protective equipment or tool to prevent the spread of COVID-19. However, mask-wearing remains a complicated issue, significantly since US Centers for Disease Control and Prevention (CDC) relaxed its guidance about outdoor mask-wearing for people who have been fully vaccinated. CNN, as a media, reported that the mask-wearing issue is confusing and causing controversies. This study uncovered the political issue, ideology, power, culture, and economics. After using the Fairclough approach, there are economic and political issues found between the US and China, which affect CDC in making decisions or regulations about mask-wearing.